Sistem Pengelolaan Transaksi Toko Perhiasan Perak Berbasis Desktop (Studi Kasus: Toko Perak Beben Banjarmasin) - Nadya Ramadana; Denny Sagita Rusdianto; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Toko Perhiasan Beben is a store that sells and buys silver either as silver raw materials or jewelry goods. Silver jewelry goods that Toko Perhiasan Beben sells such as bracelets, necklaces, ear rings, rings, ankle band and brooches. In this store, there is two transactions available, which is selling goods and buying goods. In analysis result, transactions in this store still are handled in conventional ways, no report about financial, and no report on quantity of goods. Besides selling goods on its own store, Toko Perhiasan Beben also has third party seller (sales). The owner wants to have reminder for the sales to pay goods that he/she buys when he/she can't pay up in 30 days. To solve these problems, researcher make suggestion to implement a management system on silver jewelry goods based on desktop. With primal function in selling and buying management transactions, stocks management, financial statements and sales payment. This research is started by requirements gathering which analyzed to 28 functional from the system. The next step is to make a design and implementation. System is implemented using java language and Model, View, Controller (MVC) as design pattern with database MySQL. After implementation is finished, the system will be tested using whitebox testing and blackbox testing. The whitebox testing will be done using unit testing and the blackbox testing will be done using validation testing. Testing result of this implemented system is 100 percent valid as the system is compatible with analysis and design result.